(untitled) (Journal of the College of Basic Education, 2022)
And prayers and peace be upon the honest and trustworthy Messenger Muhammad and his pure and honorable household and his chosen and chosen companions.The lack of codification for a long time in the Arabian Peninsula played a major role in the loss and dispersal of lineages there, but in fact led to the loss of history itself in most of its regions and not only the lineages that are part of this history, and the researcher notes the extent of overlap and inaccuracy in the genealogy of many tribes of the island Arab to the extent that it is not possible to determine the lineage of some tribes, whether they are Qahtaniya or Adnaniya, as well as many branches of these tribes, due to the overlap in the alliance.